Early Portraits of Government Policy in Dealing with Covid-19 in Indonesia - Ria Fitriani; Luqman Hakim; Oscar Radyan Danar (Sekolah Pascasarjana Universitas Brawijaya, 2021)
Covid-19 as a non-natural disaster has captured the world's attention and demands the government to give its best efforts in dealing with this virus and all the problems that are its side effects. Therefore, handling Covid-19 cannot be separated from public policy studies. Its emergence is a slap in the face of the government and society regarding the importance of a disaster management system. This paper aims to analyze the government's efforts in dealing with the Covid-19 epidemic through the perspective of public policy in the last 7 months (March-October 2020). This paper describes aspects that are the focus of discussion, including the responsiveness of the government in handling Covid-19, the polemic of health and economic interests, and the organizational capacity and participation of the wider community. The research method used in this research is media content analysis and literature study, which includes scientific literature, government speeches and reports, as well as mass and social media platforms.